Konstruksi Makna Pulang dalam Antologi Puisi Masih Ingatkah Kau Jalan Pulang Karya Damono dan Sedu: Perspektif Peirce - Nadia Bella Mulkillah; Suminto A. Sayuti; Wiyatmi Wiyatmi (Universitas Nahdlatul Wathan Mataram, 2026)
This study examines the construction the meaning of the word Pulang in the poetry anthology Masih Ingatkah Kau Jalan Pulang by Sapardi Djoko Damono and Rintik Sedu trought the Triadik (Representamen, Object and Interpretant) Semiotics of Charles Sander Peirce. Employing a descriptive qualitative approach and semiotic analysis, the study focuses on ten poems is Waktu, Kau, Demikianlah, Masih, Tapi, Sudah, Ketika, Masih (2), Antara and Jalan. Data were collected through close reading and note-taking techniques and were subsequently analyzed using Peirce’s Triadic model. The findings reveal that the word Pulang does not convey a single, fixed meaning but rather generates multiple layers of interpretation. These meanings include a literal sense of returning home, an emotional sense associated with returning to affective relationships, an existential sense related to the search for direction and self-awareness, and a metaphysical sense referring to a return to the origin of life. The study demonstrates that pulang functions as an open symbol that produces complex poetic meanings through an ongoing process of semiosis. Furthermore, the findings confirm the effectiveness of Peircean semiotics in uncovering symbolic meanings in contemporary poetry. This study contributes to literary linguistics by expanding discussions on the symbolic function of words in poetry and by showing how a single lexical item can develop into a multidimensional sign within literary discourse.